2021
DOI: 10.3390/ijms222112028
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Peptides and Their Cu(II) and Ni(II) Complexes: Coordination and Biological Characteristics

Abstract: Antimicrobial peptides are a promising group of compounds used for the treatment of infections. In some cases, metal ions are essential to activate these molecules. Examples of metalloantibiotics are, for instance, bleomycin and dermcidin. This study is focused on three new pseudopeptides with potential biological activity. The coordination behavior of all ligands with Cu(II) and Ni(II) ions has been examined. Various analytical methods such as potentiometric titration, UV-Vis and CD spectroscopies, and mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
(62 reference statements)
2
4
0
Order By: Relevance
“…The blue shift in the maximum wavelength with increasing pH indicates that N amide of the peptide bonds gradually coordinates to Cu 2 + ions, and the concentration of the coordinated form, such as [N N-terminus , N imidazole , N amide ], increases at pH > 6. [16] This is in good agreement with the fact that HIT/Cu 2 + metallohydrogels are formed only at pH 4.0-6.0, and above pH 6, deep blue precipitation is observed and no gelation occurs (Figure S9). Therefore, in the higher pH region, the amides of HIT are used for coordination to Cu 2 + ions, and the β-sheet-like structure cannot be formed; consequently, no metallohydrogel is formed.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The blue shift in the maximum wavelength with increasing pH indicates that N amide of the peptide bonds gradually coordinates to Cu 2 + ions, and the concentration of the coordinated form, such as [N N-terminus , N imidazole , N amide ], increases at pH > 6. [16] This is in good agreement with the fact that HIT/Cu 2 + metallohydrogels are formed only at pH 4.0-6.0, and above pH 6, deep blue precipitation is observed and no gelation occurs (Figure S9). Therefore, in the higher pH region, the amides of HIT are used for coordination to Cu 2 + ions, and the β-sheet-like structure cannot be formed; consequently, no metallohydrogel is formed.…”
Section: Resultssupporting
confidence: 87%
“…The CD spectra of HIT at pH < 4 (i. e., acidic conditions) show a maximum around 215 nm owing to the n!π* transition, regardless of the presence or absence of Cu 2 + ions. For example, the spectra at pH 1.88 (Figure S5 UV-Vis spectral analysis showed a trend similar to that of the CD analysis, with a maximum peak at 640-700 nm due to ligand-to-metal charge-transfer transitions [16] of HIT to Cu 2 + at pH 4-8 (Figure S6), indicating the formation of histamine-type [N N-terminus , N imidazole ] Cu 2 + /HIT 1 : 1 and 1 : 2 complexes [17] in this pH region (Figure S7). These results are consistent with the electrospray ionization time-of-flight mass spectra and 1 H NMR spectra of HIT/Cu 2 + (Figure S8 and S14).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…In another study, Kotynia and co-workers [ 5 ] identified three novel anti-microbial pseudopeptides containing the non-proteinogenic amino acids ornithine and 2,4-diaminobutyric acid. These pseudopeptides are metal chelators able to interact with copper and nickel ions.…”
mentioning
confidence: 99%
“…As an important branch of inorganic chemistry, coordination chemistry 1 is closely related to chemical fields such as organic chemistry 2 , analytical chemistry 3 , biochemistry 4 , medicinal chemistry 5 , and the chemical industry 6 . It has attracted the attention of many chemists.…”
mentioning
confidence: 99%